Statistics of bicycle rider motion - Moore, J. K.; Hubbard, M.; Schwab, A. L.; Kooijman, J. D. G.; Peterson, D. L. (Procedia Engineering, 2010)
An overview of bicycle and rider kinematic motions from a series of experimental treadmill tests is presented. The full kinematics of bicycles and riders were measured with an active motion capture system. Motion across speeds are compared graphically with box and whiskers plots. Trends and ranges in amplitude are shown to characterize the system motion. This data will be used to develop a realistic biomechanical model and control model for the rider and for future experimental design.